Parenting Styles and Resilience towards Reproductive Health in Married Female Adolescents in Gunungkidul, Yogyakarta, Indonesia - Beby Yohana; Tri Sunarsih; Dewi Rokhanawati (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: More than 700 million women were married before turning 18 in all over the world. In 2016, Gunung Kidul Regency, Yogyakarta, Indonesia, had the highest number of child marriages which accounted for 1.395 cases. Considering the many negative factors of early pregnancy, possessing the ability to survive and overcome hardship is imperative for married female adolescents. This study aimed to examine the effects of parenting style on resilience toward health reproductive.Subjects and Method: This was a cross sectional study conducted in Gunung Kidul, Yogyakarta, Indonesia. A total of 79 married female adolescents were selected for this study. The dependent variable was resilience toward reproductive health. The independent variables were age, education, employment, information source, economic status, knowledge, paternal parenting style, and maternal parenting style. The data were collected using questionnaire and analyzed by a multiple logistic regression.Results: High knowledge (OR= 3.48; 95% CI= 0.11 to 10.55; p= 0.028) and democratic parenting style (OR= 5.11; 95% CI= 1.62 to 16.05; p= 0.005) increased the resilience toward reproductive health in married female adolescents, and they were statistically significant.Conclusion: High knowledge and democratic parenting style increases the resilience toward reproductive health in married female adolescents.Keywords: resilience, reproductive health parenting styleCorrespondence: Beby Yohana. Masters Program in Midwifery, Universitas Aisyiyah Yogyakarta. Jl. Ringroad Barat No.63, Mlangi Nogotirto, Gamping, Gamping, Sleman, Yogyakarta, Indonesia Email: yohana.beby@yahoo.com. Mobile: 08112910055Journal of Health Promotion and Behavior (2020): 96-103https://doi.org/10.26911/thejhpb.2020.05.02.04